Comparison of Dynamics of Udder Skin Microbiota From Grazing Yak and Cattle During the Perinatal Period on the Qinghai–Tibetan Plateau - Jianbo Zhang; Jianbo Zhang; Anum Ali Ahmad; Yan Jia; Renqing Dingkao; Mei Du; Zeyi Liang; Juanshan Zheng; Ibrahim Bature; Ping Yan; Ghasem Hosseini Salekdeh; Xuezhi Ding; et al. (Frontiers in Veterinary Science, 2022)
The perinatal period has an important impact on the health of ruminants, and the imbalance of udder skin microbiota might be an important inducement of bovine mastitis. However, it is not clear how the perinatal period affects the microbial structure and stability of the udder skin of yak and cattle. Here, we used 16S rRNA gene high-throughput sequencing to analyze the udder skin microbiota of yak and cattle during the perinatal period. We found that the diversity and richness of microbiota of bovine udder skin during 1–2 weeks postpartum were significantly lower than those in the 1–2 weeks prenatal and 1-month postpartum period (Wilcoxon, p < 0.05). Besides, we found sharing of 2,533 OTUs in the udder skin microbiota of yak and cattle during the perinatal period, among which the core microbiota at the genera level was mainly composed of Staphylococcus, Moraxella, and Acinetobacter. However, the genus Acinetobacter was significantly abundant in the udder skin of cattle during 1–2 weeks postpartum. The NMDS and LEfSe results showed that the perinatal period had more effects on the composition and stability of microbial community in the udder skin of cattle compared to yak, particularly during 1–2 weeks postpartum. In addition, the average content of total whey proteins and immunoglobulin G of whey protein were significantly higher in the yak colostrum when compared to those found in the cattle (p < 0.05). In conclusion, the structure of udder skin microbiota of yak during the perinatal period is more stable than that of cattle in the same habitat, and 1–2 weeks postpartum may be a potential window period to prevent cattle mastitis.